Penerapan E-Learning Menggunakan Google Classroom sebagai Sarana Media Belajar di SMK Negeri 2 Tangerang Selatan - Ghema Nusa Persada; Santosa Wijayanto (Teknik Informatika Universitas Pamulang, 2021)
The process of teaching and learning activities (KBM) during the Covid-19 pandemic in schools cannot be done in the classroom, but along with technological developments it can be applied through online media. The use of e-learning using google classroom functioned as an online media with many benefits, so it is very suitable for its application in schools. The use of e-learning with google classroom is a means to complement class learning which aims to improve the competence of students. The application of this media is certainly very helpful for educators in providing material both in the form of assignments, discussions that can be carried out outside of classroom learning activities. The research conducted aims to measure the effectiveness and satisfaction level of educators in the implementation of learning through e-learning using google classroom which is applied in schools. The method of calculating the effectiveness of using the Likert scale is based on the respondent's data obtained from the questionnaire. The Importance Performance Analysis (IPA) method is used to measure the level of importance, and the Customer Satisfaction Index (CSI) is used to measure the level of satisfaction. The use of e-learning with googles is a means of learning in schools to get very effective results. The results of the calculations are obtained based on indicators of learning planning, making teaching materials, delivery, student interaction, and learning evaluation. The level of suitability and the level of user satisfaction gets a figure above 80%, so it means that the application of e-learning is very satisfactory.